THE ROLE OF ENDOTHELIAL DYSFUNCTION AS A PART OF SYSTEMIC INFLAMMATORY RESPONSE IN PATHOGENESIS OF AGGRESSIVE AND INDOLENT NON-HODGKIN’S LYMPHOMAS - O. B. Seregina; T. N. Babaeva; T. I. Pospelova (Сибирский научный медицинский журнал, 2019)
Objective. To study of manifestation of angiogenic and hemostatic forms of endothelial dysfunction and systemic inflammatory response in patients with non-Hodgkin’s lymphomas at the onset of disease. Material and methods. A total of 99 patients were enrolled in this study, including 55 patients with aggressive variants and 44 patients with indolent variants. The average age was 60.71±10.63 years. The serum level of vascular endothelial growth factor (VEGF) was measured as a marker of angiogenic form of endothelial dysfunction, the serum levels of thrombomodulin, D-dimers, soluble fibrin-monomer complex (SFMC) and level of Willebrand factor activity were used for evaluation of hemostatic form of endothelial dysfunction. To assess the degree of systemic inflammation response the serum levels of proinflammatory cytokines – TNF-α, IL-1β, IL-6 were measured, as well as serum level of acute phase proteins – C-reactive protein (CRP), fibrinogen. The serum level of IL-4 was used to evaluate antinflammation resistance. Results and discussion. Proinflammatory cytokine (TNF-α, IL-1β and IL-6) content was higher in both studied groups compare to the control group. Serum concentration of anti-inflammatory cytokine IL-4 in studied groups did not differ from the level in the controls group. CRP and fibrinogen serum content was increased only in group of patients with aggressive variants. There was a significant correlation between the level of CRP and proinflammatory cytokines in aggressive lymphoma group. Serum content of VEGF, thrombomodulin, D-dimers, SFMC and Willebrand factor activity were increased in both studied group in comparison with the control group. Concentration of thrombomodulin, D-dimers, SFMC and Willebrand factor activity was higher in patients with aggressive than in patients with indolent lymphomas. Conclusion. The signs of angiogenic and hemostatic forms of endothelial dysfunction in patients with aggressive and indolent variants of non-Hodgkin’s lymphoma were detected, as well as manifestation of systemic inflammatory response and attenuation of anti-inflammatory resistance with development of cytokines imbalance with proinflammatory cytokines predominance. The manifestations of systemic inflammatory response and hemostatic type of endothelial dysfunction with activation of coagulation were displayed more prominently in the aggressive lymphoma group.